2000
DOI: 10.1097/00004424-200007000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Hydro-MRI in Crohn’s Disease

Abstract: Hydro-MRI seems to be superior to the CDAI and CRP for the registration of Crohn's disease activity. In particular, differentiation between an active and an inactive (scarred) stenosis, which is crucial for the choice of therapeutic procedures, seems to be more reliable by the interpretation of several morphological and functional parameters on hydro-MRI than by the use of CDAI and CRP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…It seems logical that a partly subjective index does not necessarily correlate with anatomy-based grading of disease activity. Our hypothesis is supported by earlier studies (2,38) that showed low correlation coefficients between CDEIS and CDAI, and between individual MR parameters and CDAI (28). To our knowledge, seven prospective studies have examined the accuracy of MRI for assessing CD in an adult population using endoscopy as the gold standard (27)(28)(29)(30)(31)(32)(33).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…It seems logical that a partly subjective index does not necessarily correlate with anatomy-based grading of disease activity. Our hypothesis is supported by earlier studies (2,38) that showed low correlation coefficients between CDEIS and CDAI, and between individual MR parameters and CDAI (28). To our knowledge, seven prospective studies have examined the accuracy of MRI for assessing CD in an adult population using endoscopy as the gold standard (27)(28)(29)(30)(31)(32)(33).…”
Section: Discussionsupporting
confidence: 85%
“…However, before MRI can be considered an alternative for endoscopy in CD, it should be firmly established that in addition to detecting disease activity, MRI is capable of revealing both the severity and the exact location of disease. A few prospective studies have compared MRI with endoscopy regarding the severity of disease, but only the five most recent of these studies also analyzed the accuracy of MRI for localizing disease (27)(28)(29)(30)(31)(32)(33). The results of these studies were conflicting, and the reported sensitivities and specificities varied widely from approaching endoscopic accuracy to considerable over-or underestimation of disease.…”
mentioning
confidence: 99%
“…Complications such as fistulae, phlegmons or abscesses may be more accurately diagnosed on T1-weighted FLASH images with fat saturation by the characteristic pattern of enhancement after gadolinium administration [6]. The latter sequence is additionally useful in active disease because of the marked contrast uptake in the thickened SB wall [11,12] and mesenteric lymph node enhancement [13]. As suggested by the current study and others, disease activity can be appreciated on MRE [11][12][13][14][15], and this may Intramural fat can be accurately identified when combining features from true FISP and gadoliniumenhanced 3D FLASH images with fat saturation.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) of the small bowel is a cross sectional imaging technique which provides an accurate and reproducible diagnostic evaluation. Although IBDs early changes of mucosa can be difficult to assess with MRI, the mural changes and the extra intestinal findings are evaluated with a high diagnostic accuracy [1,2].…”
Section: Introductionmentioning
confidence: 99%